Synthesis, Electro Conductivity, Thermal Stability and Antibacterial Activity of New Bis 1, 3, 4-Oxadiazole Copolymers - Munged Jabbar Mohsin (Journal of Global Pharma Technology, 2016)
A series of bis oxadiazole copolymer were synthesized. The first series was synthesized by the reaction the resorcinol with ethylbromacetate to obtain diethyl 2,2'-[benzene-1,3-diylbis(oxy)]diacetate (1). Compound 1 was converted to their corresponding di hydrazide (2). This compound was reacted with oxalyl chloride in pyridine and N-Methyl-2-pyrrolidone (NMP) to obtained P1. This polymer was converted to P2 by cyclized it in the presence of polypesporic acid (PPA) as dehydrating agent to obtain P2 as bis oxadiazole copolymer. P3-P7 was synthesized by the reaction of compound 2 with five various di carboxylic acid in PPA as depicted in Scheme 1. These copolymers were characterized by IR and 1H-NMR. The electro conductivity of synthesized copolymer were tested at 20, 20000 Hz at 25, 35, 45, 55, 65, 75, 85 and 95 ̊C. Various positive and negative conductivity were recorded in most copolymers at different temperature. Thermal stability was studied for all copolymers. Copolymers 6 and 7 exhibited significant stability at 450 C. The antibacterial activity for these copolymers was tested against gram negative and gram positive bacteria. Copolymer P1, P2, P5, P6 and P7 showed antibacterial activity against all bacteria under test and P5 exhibited highest inhibition zone (23 mm) against Shigella dysentery, while P7 showed same inhibition against Bacillus subtilis. Furthermore, P7 exhibited inhibition zone equal 19 mm against Esherichia Coli.Keyword: Copolymer, Bis oxadiazole, Electro conductivity thermal.